2012
DOI: 10.1167/iovs.11-9316
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Glial Cells in the Autoregulation of Optic Nerve Head Blood Flow in Rabbits

Abstract: PURPOSE.To investigate the involvement of glial cells in the autoregulation of optic nerve head (ONH) blood flow in response to elevated intraocular pressure (IOP).METHODS. Rabbit eyes were treated with an intravitreal injection of L-2-aminoadipic acid (LAA), a gliotoxic compound. Twenty-four hours after the injection IOP was artificially elevated from a baseline of 20 to 50 or 70 mm Hg and maintained at each IOP level for 30 minutes. ONH blood flow was measured by laser speckle flowgraphy every 10 minutes. Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Indeed, another previous report showed that LAA at a concentration of 200 mM caused neural damage and significantly affected the ERG b-wave at 24 hours in rabbits. 17 In our preliminary experiment, we also confirmed that LAA at a concentration of 200 mM caused a significant reduction in the amplitude of the ERG b-wave in cats (data not shown). However, some reports have suggested that the implicit time of the ERG b-wave was not prolonged significantly after injections of low concentrations of LAA despite changes in the Müller cells and astrocytes.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Indeed, another previous report showed that LAA at a concentration of 200 mM caused neural damage and significantly affected the ERG b-wave at 24 hours in rabbits. 17 In our preliminary experiment, we also confirmed that LAA at a concentration of 200 mM caused a significant reduction in the amplitude of the ERG b-wave in cats (data not shown). However, some reports have suggested that the implicit time of the ERG b-wave was not prolonged significantly after injections of low concentrations of LAA despite changes in the Müller cells and astrocytes.…”
Section: Discussionsupporting
confidence: 68%
“…27 The 24-hour time course after intravitreal injection of LAA was chosen because pathologic changes and dysfunction on the ERGs were not observed in the neural retina, although the Müller cells had some damage, that is, pale stained nuclei and increased glycogen granules 24 hours after the LAA injections. 17,27 Changes in RBF to Flicker Stimulation…”
Section: Intravitreal Injections and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies supporting the autoregulatory capacity have been performed in healthy humans, nonhuman primates, cats, and rabbits. [17][18][19][20][21][22][23][24][25] The mechanisms that mediate this autoregulatory response in the ONH are unclear. Nitric oxide (NO) is a potent vasodilator that is involved in the maintenance of basal vascular tone, in tonic blood pressure regulation, and in the distribution of blood flow.…”
Section: Methodsmentioning
confidence: 99%